Xanthogranuloma of the External Auditory Canal Mimicking a Benign Tumor: A Case Report - Keisuke Yoshihama; Yasumasa Kato; Yuh Baba (Case Reports in Otolaryngology)
Exostosis, osteoma, and adenoma are the most commonly encountered benign lesions in the external auditory canal. Herein, we report a case of the mass arising from the external auditory canal in a 24-year-old Japanese man. CT revealed the soft tissue mass without bony erosion, and MRI revealed that the mass showed a homogenous, iso signal intensity on a both T1- and T2-weighted image, suggesting that the mass is a benign tumor such as adenoma. Pathological examination showed that the specimen demonstrated xanthogranuloma in the external auditory canal. Although xanthogranuloma of the external auditory canal is extremely rare, otolaryngologists should recognize this condition during the inspection of the external auditory canal.